The Prevalence of Neck and Shoulder Symptoms and Associations with Comorbidities and Disability: The Johnston County Osteoarthritis Project - Wright, Anne R. (Myopain, 2016)
OBJECTIVES: Neck and shoulder pain are common but underreported by older people, raising important questions of frequency, medical comorbidities, gender and racial disparities and functional impact associated with neck and shoulder symptoms in elders, which we examined in this analysis. METHODS: We performed a cross-sectional analysis in the community-based Johnston County Osteoarthritis Project, a cohort that is representative of the U.S. population, utilizing data from 1672 participants with a mean age of 68 years; 69% were white and 68% were women. Trained staff obtained data on participant-reported: symptoms, comorbidities, depression, and functional status; and performance-based functional assessments. Regression models of neck and shoulder symptoms and functional measures were adjusted for age, sex, race, and body mass index, and additionally for other joint symptoms and comorbidities. RESULTS: Symptoms of neck (8%), shoulder (13%) or both (13%) were reported by participants. Neck symptoms were most frequently reported by White women; shoulder symptoms were evenly distributed among race and gender subgroups. Neck and shoulder symptoms were associated with cancer, diabetes mellitus, depression, and lung, cardiovascular, and other musculoskeletal problems, as well as pain, aching or stiffness at other sites, and independently with self-reported and performance –based functional measures. CONCLUSIONS: These findings suggest that primary health care providers should inquire about neck and shoulder symptoms and address potential underlying causes to improve functional status and decrease disability in older people.